Starting the Conversation: Are Campus Sexual Assault Policies Related to the Prevalence of Campus Sexual Assault?. Issue 21 (November 2018) - DeLong, Stephanie M.; Graham, Laurie M.; Magee, Erin P.; Treves-Kagan, Sarah; Gray, Christine L.; McClay, Alison M.; Zarnick, Samantha M.; Kupper, Lawrence L.; Macy, Rebecca J.; Ashley, Olivia S.; Pettifor, Audrey; Moracco, Kathryn E.; et al.
One goal of university campus sexual assault (CSA) policies is to help prevent CSA. Federal guidance in the 2014 White House Task Force to Protect Students From Sexual Assault Checklist for Campus Sexual Misconduct Policies suggests 10 elements for inclusion in CSA policies (e.g., Policy Introduction, Grievance/Adjudication), and outlines policy topics to be included within each element (Policy Introduction includes two topics: statement of prohibition against sex discrimination including sexual misconduct and statement of commitment to address sexual misconduct). However, no research has examined whether CSA policies impact CSA prevalence. To begin addressing this gap, we studied 24 universities participating in the 2015 Association of American Universities Campus Climate Survey on Sexual Assault and Sexual Misconduct. We linked 2014-2015 data from these universities' CSA policies and their CSA prevalence findings from the 2015 Association of American Universities (AAU) survey. To test whether the comprehensiveness of schools' CSA policies was related to schools' CSA prevalence, we examined the degree to which the CSA policies included recommended policy content from the aforementioned Checklist . Policies were characterized as more comprehensive if they included greater numbers of Checklist topics. We then correlated the number of topics within the policies with school-level CSA prevalence. We also explored whether there was lower CSA prevalence among schools with policies containing particular topics. Results suggested that greater comprehensiveness of schools' entire CSA policies was negatively correlated with CSA prevalence; however, these findings did not approach statistical significance. The number of negative correlations observed between schools' CSA policy elements and CSA prevalence among undergraduate women was greater than expected by chance alone, suggesting a possible connection between comprehensive CSA policies and CSA prevalence. Schools with policies that included a topic on their sexual assault response team had the lowest CSA prevalence for both women and men, and schools that included topics describing grievance/adjudication procedures had lower CSA prevalence. This study provides a novel examination of CSA and could inform needed research related to the impact of CSA policies on CSA.